Profitability, Leverage, and Dividend Policy: Determinants of Stock Return Levels of Indonesian Banks - Safitri, Niluh Santi; Indrawati, Nur Khusniyah; Champaca, Mychelia (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
The banking and financing sector plays a pivotal role in capital markets, where stock returns are influenced by internal financial indicators such as profitability and leverage. However, the role of dividend policy as a mediating mechanism remains debatable. This study aims to analyze the effect of profitability and leverage on stock returns, with dividend policy as a mediating variable, in bank and financing institution companies listed on the Indonesia Stock Exchange. Employing a quantitative approach, the study uses path analysis on 16 companies over the periods 2016–2019 and 2022–2023, totaling 96 observations. Profitability is measured by Return on Equity (ROE), leverage by Debt-to-Equity Ratio (DER), dividend policy by Dividend Payout Ratio (DPR), and stock returns by capital gains and dividend yield. The findings reveal that profitability and leverage significantly and positively influence both stock returns and dividend policy. Moreover, dividend policy significantly mediates these relationships but has a negative effect on stock returns. These results align with signaling and trade-off theories but contradict the bird in the hand theory. The study concludes that investors prioritize growth through retained earnings over cash dividends in this sector.